Анатомічні та валеологічні знання як чинник оптимізації практики інклюзивного освітнього середовища - Білан Валентина; Bilan Valentyna; Бевзюк Марина; Bevziuk Maryna (Видавництво «Код», 2025)
Резюме. У статті розглядаються теоретичні та практичні аспекти впровадження анатомічних та валеологічних знань у практику інклюзивного освітнього середовища. Проаналізовано сутність анатомічних та валеологічних знань як важливого чинника формування здоров’язбережувальних компетентностей учнів з особливими освітніми потребами. Обґрунтовано значення анатомічного та валеологічного підходу для гармонійного поєднання освітніх і корекційно-розвивальних завдань у школі, що сприяє збереженню та зміцненню фізичного і психічного здоров’я, розвитку соціальної активності та підвищенню рівня адаптації дітей до навчального середовища.

Abstract. The article discusses the theoretical and practical aspects of implementing anatomical and valeological knowledge into the practice of an inclusive educational environment. The essence of anatomical and valeological knowledge as an important factor in the formation of health-saving competencies of students with special educational needs is analyzed. The importance of the anatomical and valeological approach for the harmonious combination of educational and corrective-developmental tasks at school is substantiated, which contributes to the preservation and strengthening of physical and mental health, the development of social activity, and an increase in the level of adaptation of children to the educational environment. Particular attention is focused on the need to integrate anatomical and valeological components into the educational process through the use of modern health-saving technologies, innovative methods, and individually-oriented approaches. The main directions of methodological support for teachers have been identified, in particular, improving their valeological competence, improving the forms and methods of educational work, and cooperating with parents and specialists from inclusive resource centers. It is concluded that the implementation of anatomical and valeological knowledge into the practice of inclusive education requires comprehensive interaction between all participants in the educational process and the creation of a favorable inclusive environment that will ensure effective learning, upbringing, and development of children with special educational needs.
Anatomical and physiological knowledge as a factor in optimizing inclusive educational environments
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: анатомія людини; валеологічна освіта; фізичне виховання; інклюзивна освіта; діти шкільного віку; заклад загальної середньої освіти